(untitled) (Perner’s Contacts, 2016)
The article deals with the detection of the postal transport cage while passing through the RFID gate depending on the RFID tag and its position. Two different tags were tested namely active RFID-tag-MET96 and passive tag HA-VIS FT 89. Both RFID tags are constructed for identification of metal objects.